Analysis of the uzbek tale yoriltosh (split stone) with the max lüthi method - ELİF EZGİ DEMİR GÜRDÜN (Uluslararası Türk Lehçe Araştırmaları Dergisi, 2023)
The tale has been a cultural carrier for centuries by being transferred from generation to generation. This literary genre, which is a product of oral culture, includes motifs related to its geography, culture and tradition. The spread of the tale to different cultures also contributes to intercultural transfer. A lot of research has been done on fairy tales and analysis methods have been put forward. Swiss literary theorist Max Lüthi’s method based on European fairy tales is one of these examination methods. M. Lüthi deals with the tales according to the items of one-dimensionality, depthlessness, abstract styll, isolation and universal interconnection with all the sublimation and all-inclusiveness. In Turkey, 2 translated articles, 1 paper, 5 articles, 1 doctoral thesis, 1 book and 1 master's thesis were written about Max Lüthi’s method. The studies carried out only cover the tales in Turkish. No study has been done on the tales that exist in the Turkic Republics. In this study, the Uzbek tale Yoriltosh was examined with the method of Max Lüthi and the universal validity of the tale was questioned.